Lean Manufacturing Implementation through Value Stream Mapping on Gold Products - Simamora, Asfhanda; Insanita, Rizqiah (Fakultas Ekonomi Universitas Samudra, 2024)
The manufacturing process at UBPP Precious Metal Manufacturing Bureau involves many wasteful activities such as manual production records, lack of standardization and digitization, which can lead to lost time and non-conformities if something goes wrong. The purpose of the study is to identify and eliminate wastes in the manufacturing process using Value Stream Mapping (VSM) to achieve lean manufacturing. VSM approach to understand gold manufacturing mapped in the current state map and improvements applied to the future state map. The cycle time in the weight check, cleaning, press and engraving process for the gramasi variant is still above 7.2 seconds per pcs with a daily target of 9,000 pieces. Proposed improvements to eliminate waste such as equipment re-layout, rejuvenation of rolling equipment, punch, press, engraving can reduce cycle time below the targeted takt time.